2016
DOI: 10.1128/jvi.02482-15
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Positively Charged Residues in Enterovirus 71 Capsid Protein VP1 Essential for Production of Infectious Particles

Abstract: Enterovirus 71 (EV71), a positive-stranded RNA virus, is the major cause of hand, foot, and mouth disease (HFMD) in children, which can cause severe central nervous system disease and death. The capsids of EV71 consist of 60 copies of each of four viral structural proteins (VP1 to VP4), with VP1, VP2, and VP3 exposed on the surface and VP4 arranged internally. VP1 plays a central role in particle assembly and cell entry. To gain insight into the role of positively charged residues in VP1 function in these proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
2
26
1
Order By: Relevance
“…The importance of having positively charged residues at the 5-fold axis of VP1 has been shown to be crucial for production of infectious particles (10). However, we provide evidence that suggests K244E mutants can produce infectious virus and do in fact replicate in mice (Fig.…”
Section: Figcontrasting
confidence: 39%
See 4 more Smart Citations
“…The importance of having positively charged residues at the 5-fold axis of VP1 has been shown to be crucial for production of infectious particles (10). However, we provide evidence that suggests K244E mutants can produce infectious virus and do in fact replicate in mice (Fig.…”
Section: Figcontrasting
confidence: 39%
“…K244E did not produce virus whose titer could be determined on RD cells by TCID 50 . A similar phenomenon was observed when position 244 of VP1 was mutated from a lysine to another amino acid in previous EV71 studies (10,14). We concluded that the mutant virus was not viable and hypothesized that a positively charged residue at position 244 was needed to produce infectious virus.…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations